Managing a web portal adapting to new technologies - Kim, Soonho; Kincheloe, Kathryn Pace; Gao, Yuan; Berisha, Valdete (2014)
This paper presents a study of how new technologies can help manage web content and outreach activities in the context of capacity building in agricultural economics. The Web portal of the African Growth and Development Policy Modeling Consortium (AGRODEP), facilitated by IFPRI, was developed to serve as an online repository to access economic modeling tools, data, documents and events. To achieve these objectives, the Web portal has been adapting technologies including Drupal for content management, Google Analytics for web log analysis, social media for outreach via e-newsletters and bulletins, and Schema.org, which creates better visibility of AGRODEP members in web search engine results. Possible steps to further improve the AGRODEP Web portal include bringing external contents from Linked Open Data and mashup into the AGRODEP portal as a way to provide more relevant and up-to-date information to AGRODEP members.